Optical Glass and Optical Elements

JP7660239B2Active Publication Date: 2025-04-10HOYA CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024025684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-07-20
Filing Date
2024-02-22
Publication Date
2025-04-10
Estimated Expiration
2038-07-02

Smart Images

  • Figure 0007660239000001
    Figure 0007660239000001
  • Figure 0007660239000002
    Figure 0007660239000002
  • Figure 0007660239000003
    Figure 0007660239000003
Patent Text Reader

Abstract

To provide an optical glass and an optical element having a reduced reduction color.SOLUTION: There is provided an optical glass which contains 1 to 45 mass% of B2O3 and 10 to 60 mass% of La2O3, contains at least one oxide selected from the group consisting of TiO2, Nb2O5, WO3 and Bi2O3 and has a value of βOH represented by the following expression (2) of 0.1 to 2.0 mm-1: βOH=-[ln(B / A)] / t...(2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical glass and an optical element. [Background technology]

[0002] 2. Description of the Related Art In recent years, as imaging optical systems, projection optical systems, and other devices have become more sophisticated and more compact, there has been an increasing demand for optical glasses with high refractive indices as effective optical element materials.

[0003] High refractive index optical glass such as that described in Patent Document 1 usually contains large amounts of high refractive index components such as Ti, Nb, W, Bi, etc. These components are easily reduced during the glass melting process, and these reduced components absorb light on the short wavelength side of the visible light range, causing coloring of the glass (hereinafter sometimes referred to as "reduced color"). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-112697 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above circumstances, and has an object to provide an optical glass and an optical element with reduced reduction color. [Means for solving the problem]

[0006] The gist of the present invention is as follows. [1] B 2 O 3 1 to 45 mass% of La 2 O 3 Contains 10 to 60 mass% TiO 2 , Nb 2 O 5 , WO3 and Bi 2 O 3 At least one oxide selected from the group consisting of The value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 That is, optical glass. βOH=-[ln(B / A)] / t …(2) (In formula (2), t represents the thickness (mm) of the glass used in measuring the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to the thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to the thickness direction. In addition, ln is the natural logarithm.)

[0007] [2] SiO 2 The optical glass according to [1], comprising 0.1 to 25 mass % of

[0008] [3] SiO 2 0.5 to 15 mass% of B 2 O 3 1 to 30 mass% of La 2 O 3 The optical glass according to [1], comprising 20 to 60 mass % of

[0009] [4] In mass %, B 2 O 3 The content of SiO 2 The content of [1] to [3] is greater than that of The optical glass according to any one of the above.

[0010] [5] B 2 O 3 and La 2 O 3 TiO relative to the total content 2 Mass ratio of the content [TiO 2 / (B 2 O 3 +La 2 O 3 The optical glass according to any one of [1] to [4], wherein the refractive index (R) is 0.030 or more.

[0011] [6] The Abbe number νd is 20 to 45; The optical glass according to any one of [1] to [5] above, having a refractive index nd of 1.75 to 2.50.

[0012] [7] An optical element comprising the optical glass according to any one of [1] to [6] above. Effect of the Invention

[0013] According to the present invention, it is possible to provide an optical glass and an optical element with reduced reduction color. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, one embodiment of the present invention will be described. In the present invention and this specification, the glass composition is expressed on an oxide basis unless otherwise specified. Here, the "glass composition on an oxide basis" refers to a glass composition obtained by converting the glass raw materials into those that are all decomposed during melting and exist as oxides in the glass, and the notation of each glass component is conventionally as follows: SiO 2 , TiO 2 The glass component contents and total contents are based on mass unless otherwise specified, with "%" meaning "% by mass" and "ppm" meaning "ppm by mass".

[0015] The content of the glass component can be quantified by known methods, such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), etc. In this specification and the present invention, the content of a component being 0% means that the component is substantially not contained, and it is acceptable for the component to be contained at an unavoidable impurity level.

[0016] In this specification, unless otherwise specified, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).

[0017] The Abbe number νd is used as a value representing the properties related to dispersion, and is expressed by the following formula (1), where nF is the refractive index at the F line (wavelength 486.13 nm) of blue hydrogen, and nC is the refractive index at the C line (656.27 nm) of red hydrogen. νd=(nd-1) / (nF-nC) (1)

[0018] The optical glass according to the embodiment of the present invention is B 2 O 3 1 to 45 mass% of La 2 O 3 Contains 10 to 60 mass% TiO 2 , Nb 2 O 5 , WO 3 and Bi 2 O 3 At least one oxide selected from the group consisting of The value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 It is. βOH=-[ln(B / A)] / t …(2) (In formula (2), t represents the thickness (mm) of the glass used in measuring the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to the thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to the thickness direction. In addition, ln is the natural logarithm.)

[0019] The optical glass according to this embodiment (hereinafter sometimes simply referred to as "glass") will be described in detail below.

[0020] The glass according to this embodiment is B 2 O 3 Contains 1-45%. B 2 O 3 The lower limit of the content of B is preferably 2%, more preferably 3%, 4%, and 6% in that order. 2 O 3The upper limit of the content is preferably 30%, and more preferably 25%, 20%, and 15%, in that order.

[0021] B 2 O 3 is a glass network forming component, which maintains low dispersion and improves the thermal stability of the glass. 2 O 3 If the content of B is high, the amount of volatilization of glass components during glass melting may increase. Also, the devitrification resistance tends to decrease. 2 O 3 The content is preferably within the above range.

[0022] The glass according to this embodiment is 2 O 3 Contains 10-60% La 2 O 3 The lower limit of the content of La is preferably 20%, more preferably 22%, 24%, 27%, and 30% in that order. 2 O 3 The upper limit of the content is preferably 57%, more preferably 55% and further more preferably 53%.

[0023] La 2 O 3 has the function of increasing the refractive index nd. It also has the function of increasing the chemical durability. 2 O 3 When the content of La increases, the specific gravity increases and the thermal stability of the glass decreases. 2 O 3 It is preferable that the content is within the above range.

[0024] The glass according to this embodiment is made of TiO 2 , Nb 2 O 5 , WO 3 and Bi 2 O 3 At least one oxide selected from the group consisting of TiO 2 , Nb 2 O 5 , WO3 and Bi 2 O 3 All of these are components that contribute to a high refractive index, and by containing these components, an optical glass with a high refractive index can be obtained.

[0025] In the glass according to this embodiment, the value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 The lower limit of the value of βOH is preferably 0.2 mm -1 and even 0.25 mm -1 , 0.3mm -1 , 0.35mm -1 The upper limit of the βOH value is preferably 1.8 mm. -1 and even 1.6mm -1 , 1.5mm -1 , 1.4mm -1 , 1.2mm -1 The order of preference is: βOH=-[ln(B / A)] / t …(2)

[0026] In the above formula (2), t represents the thickness (mm) of the glass used to measure the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to its thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to its thickness direction. In addition, in the above formula (2), ln is the natural logarithm. The unit of βOH is mm -1 It is.

[0027] The "external transmittance" is the ratio (Iout / Iin) of the intensity Iout of transmitted light through glass to the intensity Iin of incident light entering the glass, i.e., the transmittance taking into account surface reflection on the glass surface, and is obtained by measuring the transmission spectrum using a spectrophotometer.

[0028] βOH represented by the above formula (2) means absorbance due to hydroxyl groups. Therefore, by evaluating βOH, the content of water (and / or hydroxide ions, hereinafter simply referred to as "water") in glass can be evaluated. In other words, glass with a high βOH means that the water content in glass is high.

[0029] By increasing the water content in the glass and increasing the βOH value, reduction color is reduced and the annealing treatment time can be shortened. In addition, defoaming and clarification effects can be obtained. On the other hand, if the βOH value is too high, the amount of volatile matter from the molten glass tends to increase. Therefore, it is preferable to set the βOH value in the above range.

[0030] The method for increasing the βOH of glass is not particularly limited, but examples thereof include performing an operation to increase the water content in the molten glass in the melting step. Examples of the operation for increasing the water content in the molten glass include a process of adding water vapor to the melting atmosphere and a process of bubbling a gas containing water vapor into the melt.

[0031] (Glass component) The glass components other than those described above in this embodiment will be described in detail below.

[0032] In the glass according to this embodiment, SiO 2 The lower limit of the content of SiO is preferably 0.1%, and more preferably 0.5%, 1%, 1.5%, 2%, and 3% in that order. 2 The upper limit of the content is preferably 25%, and more preferably 15%, 10%, 8%, and 7%, in that order.

[0033] SiO 2 is a glass network forming component, and has the function of improving the thermal stability, chemical durability, and weather resistance of glass. 2 If the content of SiO is large, the devitrification resistance of the glass may decrease. 2 It is preferable that the content is within the above range.

[0034] In the glass according to this embodiment, P 2 O 5 The content of is preferably less than 7%, more preferably 5% or less, 4% or less, 3% or less, 2% or less, and 1% or less in that order. 2 O 5 The content may be 0%.

[0035] P 2 O 5 is a component that reduces the refractive index nd and also reduces the thermal stability of the glass. 2 O 5 It is preferable that the content is within the above range.

[0036] In the glass according to this embodiment, Al 2 O 3 The content of Al is preferably 5% or less, more preferably 4% or less, 3% or less, 2% or less, and 1% or less in that order. 2 O 3 The content may be 0%.

[0037] Al 2 O 3 is a glass component that improves the chemical durability and weather resistance of glass, and can be considered as a network forming component. 2 O 3 When the content of Al is large, the devitrification resistance of the glass is reduced. In addition, problems such as an increase in the glass transition temperature Tg and a decrease in thermal stability are likely to occur. 2 O 3 The content is preferably within the above range.

[0038] In the glass according to this embodiment, SiO 2 and B. 2 O 3 The total content [SiO 2 +B 2 O 3 The lower limit of the total content [SiO2 +B 2 O 3 The upper limit of is preferably 35%; Furthermore, the more preferable order is 30%, 26%, 24%, and 22%.

[0039] SiO 2 and B. 2 O 3 is a component that forms a glass network and improves the thermal stability and devitrification resistance of glass. 2 and B. 2 O 3 The total content [SiO 2 +B 2 O 3 ] is preferably in the above range.

[0040] In the glass according to this embodiment, preferably B 2 O 3 Content of [B 2 O 3 ] is SiO 2 Content of [SiO 2 ] is greater than ([B 2 O 3 ]>[SiO 2 More preferably, B 2 O 3 The content of SiO 2 The content of [B 2 O 3 ]>[SiO 2 ]×1.3). B 2 O 3 The content of SiO 2 By making the content larger than the content of 1, the Abbe number can be increased.

[0041] In the glass according to this embodiment, the upper limit of the ZnO content is preferably 30%, more preferably 25%, 20%, 15%, 10%, 7%, and 5% in that order. The ZnO content is preferably more than 0%, and the lower limit is more preferably 0.1%, more preferably 0.3%, 0.5%, and 1% in that order.

[0042] ZnO is a glass component that improves the thermal stability of glass and improves the melting property and chemical durability of glass. On the other hand, if the content of ZnO is too high, the specific gravity increases. Therefore, the content of ZnO is preferably within the above range.

[0043] In the glass according to this embodiment, the upper limit of the BaO content is preferably 20%, more preferably 19%, 18%, 17%, and 16%, in that order. The lower limit of the BaO content is preferably 0%, more preferably 2%, 5%, and 10%, in that order.

[0044] BaO is a glass component effective for maintaining a high refractive index, and also has the function of improving the thermal stability and devitrification resistance of the glass. On the other hand, if the content is large, the specific gravity increases and the devitrification resistance decreases. Therefore, the content of BaO is preferably within the above range.

[0045] In the glass according to this embodiment, the upper limit of the MgO content is preferably 5%, and more preferably 4%, 3%, 2%, and 1% in that order. The lower limit of the MgO content is preferably 0%.

[0046] In the glass according to this embodiment, the upper limit of the CaO content is preferably 10%, and more preferably 8%, 6%, 4%, and 2%, in that order. The lower limit of the CaO content is preferably 0%.

[0047] In the glass according to this embodiment, the upper limit of the SrO content is preferably 7%, and more preferably 5%, 4%, 3%, and 1%, in that order. The lower limit of the SrO content is preferably 0%.

[0048] MgO, CaO, and SrO are glass components that improve the thermal stability and devitrification resistance of the glass. On the other hand, if the content of these glass components is large, the specific gravity increases, the high dispersibility is impaired, and the thermal stability and devitrification resistance of the glass are reduced. Therefore, it is preferable that the content of each of these glass components is within the above-mentioned range.

[0049] In the glass according to this embodiment, Gd 2 O 3 The upper limit of the content of Gd is preferably 35%, and more preferably 30%, 25%, 20%, 17%, and 12%, in that order. 2 O 3 The lower limit of the content is preferably 0%, and more preferably 1%, 3%, 4%, and 5% in that order.

[0050] In the glass according to this embodiment, Y 2 O 3 The upper limit of the content of Y is preferably 25%, and more preferably 20%, 15%, 10%, 7%, and 5% in that order. 2 O 3 The lower limit of the content is preferably 0%, and more preferably 1%, 2%, and 3% in that order.

[0051] Gd 2 O 3 and Y 2 O 3 are all components that contribute to improving the weather resistance and increasing the refractive index of the glass. On the other hand, if the content is too high, the thermal stability of the glass decreases, and the glass becomes more susceptible to devitrification during production. Therefore, the content of each of these glass components is preferably within the above-mentioned range.

[0052] In the glass according to this embodiment, Yb 2 O 3 The upper limit of the content of Yb is preferably 5%, and more preferably 4%, 3%, 2%, and 1% in that order. 2 O 3 The lower limit of the content is preferably 0%.

[0053] Yb 2 O 3 is a component that contributes to improving weather resistance and increasing the refractive index. 2 O 3 La 2 O 3 , Gd 2 O 3 , Y 2 O 3 Since Yb ​​has a larger molecular weight than Yb, it increases the specific gravity of the glass. When the specific gravity of the glass increases, the mass of the optical element increases. For example, if a lens with a large mass is incorporated into an autofocus imaging lens, the power required to drive the lens during autofocus increases, causing rapid battery consumption. 2 O 3 It is desirable to reduce the content of to suppress an increase in the specific gravity of the glass.

[0054] In the glass according to this embodiment, ZrO 2 The upper limit of the content of ZrO is preferably 18%, and more preferably 15%, 12%, 10%, 8%, and 7% in that order. 2 The lower limit of the content is preferably 0%, and more preferably 1%, 2%, and 3% in that order.

[0055] ZrO 2 is a component that contributes to increasing the refractive index and is a glass component that works to improve the thermal stability and devitrification resistance of glass. 2 If the content is too high, the thermal stability tends to decrease. 2 The content is preferably within the above range.

[0056] In the glass according to this embodiment, TiO 2 The content of TiO is preferably more than 0%, and the lower limit is more preferably 0.1%, and further more preferably 1%, 3%, 4%, and 5% in that order. 2 The upper limit of the content is preferably 30%, and more preferably 25%. %, 23%, 21%, and 20% are more preferable in that order.

[0057] TiO 2 is a component that contributes to a high refractive index and also improves chemical durability. 2 If the content of TiO is too high, the devitrification resistance may decrease. 2 It is preferable that the content is within the above range.

[0058] In the glass according to this embodiment, Nb 2 O 5 The lower limit of the Nb content is preferably 0.1%, more preferably 1%, 3%, 4%, and 5% in that order. 2 O 5 The upper limit of the content is preferably 35%, and more preferably 30%, 25%, 20%, 16%, 15%, 14%, and 12%, in that order.

[0059] Nb 2 O 5 is a component that contributes to increasing the refractive index and also improves the thermal stability and chemical durability of the glass. 2 O 5 If the content of Nb is too high, the thermal stability of the glass may decrease, and the coloring of the glass may become stronger. 2 O 5 It is preferable that the content is within the above range.

[0060] In the glass according to this embodiment, Nb 2 O 5 and TiO 2 The total content of [Nb 2 O 5 +TiO 2 The lower limit of the total content [Nb 2 O 5 +TiO 2 The upper limit of is preferably 40%, and more preferably 35%, 32%, 31%, and 30%, in that order.

[0061] Nb 2 O 5 and TiO 2 is a component that contributes to a high refractive index. 2 O 5 If the content of Nb is too high, the thermal stability and devitrification resistance of the glass are reduced. 2 O 5 and TiO 2 The total content is preferably within the above range.

[0062] In the glass according to this embodiment, WO 3 The upper limit of the content of WO is preferably 25%, and more preferably 20%, 15%, 10%, and 5% in that order. 3 The lower limit of the content is preferably 0%.

[0063] WO 3 On the other hand, WO 3 If the content of WO becomes too high, the glass will become more colored and the specific gravity will increase. 3 The content is preferably within the above range.

[0064] In this embodiment, Bi 2 O 3 The upper limit of the content of Bi is preferably 20%, and more preferably 15%, 10%, 5%, and 3% in that order. 2 O 3 The lower limit of the content is preferably 0%.

[0065] Bi 2 O 3 When contained in an appropriate amount, it has the function of improving the thermal stability of the glass. 2 O 3 Increasing the Bi content increases the coloring of the glass and also increases the specific gravity. 2 O 3 The content is preferably within the above range.

[0066] In the glass according to this embodiment, Nb2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 The total content of [Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 The upper limit of the total content [Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 The lower limit of is preferably 1.0%, and more preferably 1.5%, 5%, 10%, 13%, 13.5%, 14%, 14.5%, and 15%, in that order.

[0067] TiO 2 , WO 3 and Bi 2 O 3 is Nb 2 O 5 It is also a component that contributes to a high refractive index. Therefore, the total content [Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 ] is preferably in the above range.

[0068] In the glass according to this embodiment, B 2 O 3 and La 2 O 3 TiO relative to the total content 2 Mass ratio of the content [TiO 2 / (B 2 O 3 +La 2 O 3The lower limit of the TiO 2 content is preferably 0.030, and the lower limit is preferably 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, and 0.50, respectively. 2 / (B 2 O 3 +La 2 O 3 The upper limit of )] is preferably 1.5, and more preferably 1.0, 0.8, and 0.6 in that order.

[0069] Nb 2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 Among these, the component with the greatest effect of increasing the refractive index nd per unit content expressed by mass% is TiO 2 In addition, TiO 2 is easily reduced during the glass melting process, and TiO 2 When reduced, the transmittance in the visible short wavelength range increases significantly. On the other hand, in the glass according to this embodiment, the main component B 2 O 3 and La 2 O 3 Therefore, the problem of reduction does not occur in TiO, which significantly reduces the transmittance in the visible short wavelength region. 2 B content does not cause such problems 2 O 3 oh YobiLa 2 O 3 The total content of TiO is large, i.e., the mass ratio [TiO 2 / (B 2 O 3 +La 2 O 3 )] is preferably small.

[0070] In the glass according to this embodiment, Nb2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 TiO relative to the total content 2 Mass ratio of the content [TiO 2 / (Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 The lower limit of the mass ratio [TiO 2 / (Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 The upper limit of )] is preferably 1.00, and can also be set to 0.90, 0.80, or 0.75.

[0071] As mentioned above, TiO 2 is easily reduced during the glass melting process, and TiO 2 When Nb is reduced, the transmittance in the visible short wavelength region is likely to decrease significantly. 2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 Among the components that contribute to a high refractive index, TiO is particularly prone to causing coloration. 2 The content of TiO is high, i.e., the mass ratio [TiO 2 / (Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 Even when the above-mentioned range is satisfied, the increase in coloring can be suppressed by introducing a gas into the atmosphere in the melting step or bubbling a gas into the melt.

[0072] In the glass according to this embodiment, Ta 2 O5 The upper limit of the Ta content is preferably 25%, and more preferably 20%, 16%, 12%, 8%, and 4%, in that order. 2 O 5 The lower limit of the content is preferably 0%.

[0073] Ta 2 O 5 is a component that contributes to increasing the refractive index and also improves the thermal stability of the glass. 2 O 5 If the content of Ta is large, the thermal stability of the glass decreases, and when the glass is melted, the glass raw material is likely to remain unmelted. 2 O 5 The content is preferably within the above range.

[0074] In the glass according to this embodiment, Li 2 The upper limit of the O content is preferably 10%, and more preferably 7%, 5%, 4%, 3%, 2%, and 1% in that order. 2 The lower limit of the O content is preferably 0%.

[0075] In the glass according to this embodiment, Na 2 The upper limit of the O content is preferably 10%, and more preferably 7%, 5%, 4%, 2%, and 1% in that order. 2 The lower limit of the O content is preferably 0%.

[0076] In the glass according to this embodiment, K 2 The upper limit of the O content is preferably 10%, and more preferably 7%, 5%, 4%, 2%, and 1% in that order. 2 The lower limit of the O content is preferably 0%.

[0077] Li 2 O, Na 2 O and K 2 Both O and Li have the effect of lowering the liquidus temperature and improving the thermal stability of glass. However, if the content of these elements is high, the chemical durability and weather resistance are reduced.2 O, Na 2 O and K 2 The content of each of the O elements is preferably within the above range.

[0078] In the glass according to this embodiment, Cs 2 The upper limit of the O content is preferably 5%, more preferably 4%, 3%, 2%, and 1%, in that order. 2 The lower limit of the O content is preferably 0%.

[0079] Cs 2 O has the function of improving the thermal stability of glass, but if its content increases, the chemical durability and weather resistance decrease. 2 The content of each of the O elements is preferably within the above range.

[0080] In the glass according to this embodiment, Li 2 O, Na 2 OK 2 O and Cs 2 Total O content [Li 2 O+Na 2 O+K 2 O+Cs 2 The upper limit of the total content [Li 2 O+Na 2 O+K 2 O+Cs 2 The lower limit of [O] is preferably 0%.

[0081] Total content [Li 2 O+Na 2 O+K 2 O+Cs 2 When the lower limit of the total content [Li O] satisfies the above, the meltability and thermal stability of the glass can be improved and the liquidus temperature can be lowered. 2 O+Na 2 O+K 2 O+Cs 2 When the upper limit of [O] satisfies the above range, a decrease in resistance to devitrification can be suppressed.

[0082] In the glass according to this embodiment, Sc 2 O 3 The content of Sc is preferably 2% or less. 2 O 3 The lower limit of the content is preferably 0%.

[0083] In the glass according to this embodiment, HfO 2 The upper limit of the content of HfO is preferably 2% or less, and more preferably 1%, 0.5%, and 0.1% in that order. 2 The lower limit of the content is preferably 0%.

[0084] Sc 2 O 3 , HfO 2 Although Sc has the effect of increasing the dispersibility of the glass, it is an expensive component. 2 O 3 , HfO 2 The content of each of the above is preferably within the above range.

[0085] In the glass according to this embodiment, Lu 2 O 3 The content of Lu is preferably 2% or less. 2 O 3 The lower limit of the content is preferably 0%.

[0086] Lu 2 O 3 Although it has the function of increasing the dispersibility of glass, it is also a glass component that increases the specific gravity of glass due to its large molecular weight. 2 O 3 The content is preferably within the above range.

[0087] In the glass according to this embodiment, GeO 2 The content is preferably 2% or less. Also, GeO 2 The lower limit of the content is preferably 0%.

[0088] GeO 2Although GeO has the function of increasing the high dispersion of glass, it is an extremely expensive component among commonly used glass components. Therefore, from the viewpoint of reducing the manufacturing cost of glass, GeO 2 The content is preferably within the above range.

[0089] The glass according to this embodiment mainly contains the above-mentioned components, that is, B as an essential component. 2 O 3 and La 2 O 3 , SiO as an optional component 2 , P 2 O 5 , Al 2 O 3 , ZnO, BaO, MgO, CaO, SrO, Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 , ZrO 2 , TiO 2 , Nb 2 O 5 , WO 3 , Bi 2 O 3 , Ta 2 O 5 , Li 2 O, Na 2 OK 2 O, Cs 2 O, Sc. 2 O 3 , HfO 2 , Lu 2 O 3 and GeO 2 The total content of the above glass components is preferably greater than 95%, more preferably greater than 98%, even more preferably greater than 99%, and even more preferably greater than 99.5%.

[0090] In this embodiment, as a further preferred embodiment, B 2 O 3 1 to 45%, La 2 O 310-60% TiO 2 Contains more than 0% of ZnO, Nb 2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 TiO relative to the total content 2 Content quality Quantity ratio [TiO 2 / (Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 )] is 0.4 or more, The value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 Examples of optical glasses include: βOH=-[ln(B / A)] / t …(2) (In formula (2), t represents the thickness (mm) of the glass used in measuring the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to the thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to the thickness direction. In addition, ln is the natural logarithm.)

[0091] In the above further preferred embodiment, B 2 O 3 , La 2 O 3 , TiO 2 and ZnO inclusion Amount, mass ratio [TiO 2 / (Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 )], and the value of βOH The above-mentioned more preferable numerical ranges can be applied to the contents and mass ratios of other glass components as well.

[0092] In the glass according to this embodiment, the platinum (Pt) content is preferably less than 10 ppm, more preferably 8 ppm or less, 7 ppm or less, and 5 ppm or less in that order. The lower limit of the Pt content is not particularly limited, but inevitably includes about 0.001 ppm.

[0093] By setting the Pt content within the above range, the coloring of the glass caused by Pt can be reduced and the transmittance can be improved.

[0094] In the manufacturing process of the glass according to this embodiment, glass raw materials are melted in a non-oxidizing atmosphere. Examples of non-oxidizing atmospheres include inert gases such as nitrogen, carbon dioxide, argon, and helium, and water vapor. Usually, oxygen in the melting atmosphere reacts with platinum, which is the material of the melting vessel (crucible, etc.), to produce platinum dioxide or platinum ions (Pt 4+ ) occurs, and dissolves in the molten glass, causing coloring. In this embodiment, by reducing the oxygen partial pressure in the melting atmosphere, it is possible to suppress the oxidation of platinum and reduce the amount of Pt that dissolves in the molten glass. As a result, it is possible to reduce coloring derived from Pt.

[0095] <Other ingredient composition> Pb, As, Cd, Tl, Be, and Se are all toxic, so it is preferable that the optical glass of the present embodiment does not contain these elements as glass components.

[0096] U, Th, and Ra are all radioactive elements, and therefore it is preferable that the optical glass of this embodiment does not contain these elements as glass components.

[0097] V, Cr, Mn, Fe, Co, Ni, Cu, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, Tm, and Ce increase the coloring of the glass and can be sources of fluorescence, so it is preferable that the optical glass of the present embodiment does not contain these elements as glass components.

[0098] Sulfate is an optional oxidizing agent that functions as a clarifier. It is decomposed by heat to produce the clarified gas SO 2 and O 2 The sulfate is not particularly limited, but examples thereof include zinc sulfate and zirconium sulfate.

[0099] The content of sulfate is expressed as an exclusive percentage. That is, when the total content of all glass components other than sulfate is taken as 100 mass%, the content of sulfate is preferably less than 1 mass%, more preferably less than 0.5 mass%, and further preferably less than 0.3 mass%. The content of sulfate may be 0 mass%.

[0100] Sb(Sb 2 O 3 ) is also an optional element that functions as a fining agent. However, Sb (Sb 2 O 3 ) is highly oxidizing, and if added in large quantities, it may accelerate the oxidation of platinum from the platinum crucible. In addition, during precision press molding, Sb (Sb 2 O 3 ) oxidizes the molding surface of the press mold, and as precision press molding is repeated, the molding surface deteriorates significantly, and there is a risk that precision press molding will become impossible. As a result, the surface quality of the molded optical element decreases. Therefore, the glass according to this embodiment preferably contains Sb (Sb 2 O 3 ) is not included.

[0101] The glass according to the present embodiment is preferably basically composed of the above glass components, but may contain other components as long as they do not impair the effects of the present invention. Furthermore, the present invention does not exclude the inclusion of unavoidable impurities.

[0102] (Glass properties) <Refractive index nd> In the glass according to this embodiment, the refractive index nd is preferably 1.75 or more, and may be 1.77 or more, or 1.80 or more. The refractive index nd is preferably 2.50 or less, and may be 2.20 or less, or 2.10 or less. The refractive index nd is determined by the following formula: 2 O 5 , TiO 2 , WO 3 and Bi 2 O 3 The total content of [Nb 2 O 5 +TiO 2 +WO 3 +Bi 2 O 3 ] can be increased by increasing SiO 2 This can be reduced by increasing the content.

[0103] <Abbe number νd> In the glass according to this embodiment, the Abbe number νd is 20 or more. The Abbe number νd may be in the range of 20 to 45, or 21 to 45. The Abbe number νd is La 2 O 3 It can be increased by increasing the content of B 2 O 3 This can be reduced by increasing the content.

[0104] <Light transmittance of glass> The light transmittance of the optical glass according to this embodiment can be evaluated by the coloring degree λ70. The spectral transmittance of a glass sample having a thickness of 10.0 mm±0.1 mm is measured in the wavelength range of 200 to 700 nm, and the wavelength at which the external transmittance becomes 70% is defined as λ70.

[0105] The λ70 of the optical glass according to this embodiment is preferably 480 nm or less, more preferably 470 nm or less, further preferably 450 nm or less, and particularly preferably 440 nm or less. λ70 can be reduced by reducing the platinum (Pt) content.

[0106] Moreover, λ70 of the optical glass according to this embodiment preferably satisfies the following formula (3). λ70≦a×b+373 (3) In the formula (3), a is preferably 200, and more preferably 195, 190, 185, 180, and 175 in that order. Also, b is B 2 O 3 and La 2 O 3 TiO relative to the total content 2 Mass ratio of the content [TiO 2 / (B 2 O 3 +La 2 O 3 )].

[0107] Mass ratio [TiO 2 / (B 2 O 3 +La 2 O 3 When (x,y) increases, the transmittance in the visible short wavelength region decreases and the coloring degree λ70 increases. In the optical glass according to this embodiment, the reduction color is reduced, and the λ70 can be suppressed within the range shown in the above formula (3).

[0108] <t450> The light transmittance of the optical glass according to this embodiment can be evaluated by T450. In this embodiment, T450 is the external transmittance at a wavelength of 450 nm when converted to a thickness of 10.0 mm. The "external transmittance" is the ratio (Iout / Iin) of the intensity Iout of transmitted light that has passed through glass to the intensity Iin of incident light that is perpendicular to one of the optically polished flat surfaces of a glass sample that has been processed to have parallel optically polished flat surfaces, that is, the transmittance taking into account the surface reflection on the glass surface. The transmittance is obtained by measuring the transmission spectrum using a spectrophotometer. The glass thickness during measurement may be 10.0 mm, but if the thickness is not 10.0 mm, the transmittance may be converted to that at a thickness of 10.0 mm using a known method.

[0109] The T450 of the optical glass according to this embodiment is preferably 65% ​​or more, more preferably 70% or more, and further preferably 75% or more. T450 can be increased by reducing the reduction color of the glass.

[0110] <t400> The light transmittance of the optical glass according to this embodiment can also be evaluated by T400. For a glass sample with a thickness of 10.0 mm ± 0.1 mm, the external transmittance T400 at a wavelength of 400 nm is measured using a spectrophotometer. It may be converted to the transmittance at a thickness of 10.0 mm using a known method. The higher the T400 value, the better the transmittance and the less coloring the glass has.

[0111] The T400 of the optical glass according to this embodiment is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more. T400 can be increased by reducing the reduction color of the glass.

[0112] <τ400> The light transmittance of the optical glass according to this embodiment can also be evaluated by τ400. For a glass sample with a thickness of 10.0 mm ± 0.1 mm, the internal transmittance τ400 at a wavelength of 400 nm is measured using a spectrophotometer. It may be converted to the transmittance at a thickness of 10.0 mm using a known method. The larger the τ400 value, the better the transmittance and the less coloring the glass has.

[0113] The τ400 of the optical glass according to this embodiment is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more. τ400 can be increased by reducing the reduction color of the glass.

[0114] <Specific gravity of glass> In the optical glass according to this embodiment, the specific gravity is preferably 7 or less, more preferably 6.5 or less, and more preferably 6 or less. The specific gravity is preferably 2.5 or more, more preferably 3 or more, and more preferably 3.5 or more. If the specific gravity of the glass can be reduced, the weight of the lens can be reduced. As a result, the power consumption of the autofocus drive of the camera lens equipped with the lens can be reduced. On the other hand, reducing the specific gravity too much leads to a decrease in thermal stability.

[0115] <Glass transition temperature Tg> The glass transition temperature Tg of the optical glass according to this embodiment is preferably 800° C. or lower, more preferably 770° C. or lower, and more preferably 750° C. or lower. The glass transition temperature Tg is preferably 300° C. or higher, more preferably 350° C. or higher, and more preferably 400° C. or higher. The glass transition temperature Tg is determined by the following formula: 2 O, Na 2 O and K 2 Total O content [Li 2 O+Na 2 O+K 2 This can be reduced by increasing the concentration of

[0116] By setting the upper limit of the glass transition temperature Tg within the above range, it is possible to suppress increases in the molding temperature and annealing temperature of the glass, thereby reducing thermal damage to press molding equipment and annealing equipment. Also, by setting the lower limit of the glass transition temperature Tg within the above range, it becomes easier to maintain the thermal stability of the glass well while maintaining the desired Abbe number and refractive index.

[0117] (Optical glass quality) Common defects in optical glass include bubbles, bumps (foreign matter), and striae. These defects are evaluated by measuring the number of defects contained in a unit amount of glass. The degree to which light transmittance is hindered changes depending on the amount of bubbles and particles present per unit cross-sectional area of ​​the glass.

[0118] However, when the unit for evaluating defects (evaluation unit) is extremely small, selecting an area that does not contain bubbles or bumps means that there are no optical defects in that range. However, optical glass generally used as an industrial product requires homogeneity over a cross-sectional area of, for example, 100mm x 100mm, or over a certain volume or more, rather than homogeneity over a very small range of, for example, 1mm x 1mm.

[0119] And not only the evaluation unit but also the production unit of optical glass should be discussed. Even if the required homogeneity is the same when making 1 ml of glass and when making 1000 kg of glass, the difficulty of manufacturing is completely different. In other words, even when melting and vitrifying the same raw materials, the amount of heat required varies depending on the amount of glass. For example, even under conditions of a melting temperature of 1250°C and a melting time of 2 hours, when making 1 ml of glass, it is possible to produce a molten liquid (molten glass) without bubbles or lumps, whereas when making 1000 kg of glass, it is difficult to even melt the raw materials.

[0120] Depending on the amount of glass, not only do the conditions required for vitrification change, but also the temperature and time required for degassing (fining) must be changed. Increasing the amount of glass increases the amount of heat required for vitrification, and the melting and fining times become longer. As a result, the amount of platinum (Pt) that makes up the crucible that dissolves into the molten glass increases.

[0121] In other words, when producing optical glass as an industrial product, the glass volume must be greater than a certain amount, and compared to experiments or small-scale glass production, the melting and fining conditions, as well as the amount of Pt that gets mixed into the glass from the production equipment (crucible, etc.) will be different.

[0122] For striae, homogeneity is an even more important characteristic. Since the defect called "striae" is a defect that discusses the optical homogeneity (spatial refractive index distribution) of a certain volume, it is necessary that the evaluation unit be a certain level or higher. Even when producing the same 1000ml of glass, the uniformity of the refractive index will be different when producing 1000ml of molten glass at once and when producing 10ml of molten glass 100 times. In general, when producing optical glass, producing 1000 ml of molten glass at once provides glass with excellent homogeneity.

[0123] As described above, optical glass that is treated as an industrial product is discussed in terms of the production volume above a certain level, and the difficulty of producing high-quality optical glass within this range and the characteristics and quality of the optical glass that depend on its manufacturing method are discussed as being inseparably linked.

[0124] The techniques discussed for very small scale (e.g. small scale laboratory) glass melting are not directly applicable to industrial scale glass melting, and the properties and quality of glass produced by different methods cannot be uniformly compared when the scale of glass production is different.

[0125] In this embodiment, in order to distinguish the characteristics and quality of experimental glass from those of industrial glass, the concept of glass homogeneity is introduced. The homogeneity of glass can be evaluated by the refractive index distribution.

[0126] <Refractive index distribution> The refractive index distribution of the optical glass according to this embodiment is preferably within 0.00050, more preferably within 0.00030, more preferably within 0.00010, more preferably within 0.00007, and even more preferably within 0.00005. The refractive index distribution is measured for a continuum having a glass volume of 100 ml or more. The glass volume of the sample used for the refractive index measurement is 1 ml or more. The volume of the glass may be calculated, for example, by measuring the mass of the glass and using the measurement result and the specific gravity.

[0127] Specifically, glass a of 100 ml or more is prepared, and the refractive index is measured at two points: an arbitrary point A and a point B opposite A. If there is a portion whose refractive index is known, that portion is designated as A, and the refractive index of the portion B furthest from A is measured. A total of two or more glass pieces are obtained from glass a, and the refractive index measurements are performed. In this embodiment, the refractive index distribution is evaluated using the refractive index nd, but the evaluation may be performed using the refractive index at other wavelengths as appropriate.

[0128] (Optical glass manufacturing) The glass according to the embodiment of the present invention may be produced by mixing glass raw materials so as to obtain the above-mentioned predetermined composition, and using the mixed glass raw materials in accordance with a known glass manufacturing method. For example, a plurality of compounds are mixed and sufficiently mixed to prepare a batch raw material, and the batch raw material is placed in a platinum crucible and roughly melted (melting step).

[0129] In the glass melting process according to the present embodiment, a reducing agent can be added to the glass raw material. The reducing agent is not particularly limited, but examples thereof include Al, Si, Ti, W, H 2 Examples of reducing agents include carbon compounds and activated carbon C. By adding a reducing agent to the glass raw material, the highly reactive oxygen generated during the vitrification of the glass raw material reacts with the reducing agent, suppressing the oxidation reaction of platinum from the platinum crucible. As a result, the Pt content in the glass can be reduced.

[0130] The melting atmosphere in the glass melting step according to this embodiment is preferably a non-oxidizing atmosphere. By performing the melting step in a non-oxidizing atmosphere, the oxygen partial pressure in the melting atmosphere is reduced, and oxidation of platinum originating from the platinum crucible is suppressed, thereby reducing the amount of Pt dissolved in the molten glass.

[0131] The non-oxidizing atmosphere is not particularly limited, but examples thereof include an inert gas atmosphere such as nitrogen, carbon dioxide, argon, helium, etc., and a water vapor-added atmosphere. In order to increase the βOH of the final glass, a water vapor-added atmosphere is preferred.

[0132] By adding water vapor to the melting atmosphere, the βOH value of the final optical glass can be increased, the dissolution of Pt and the like into the glass can be effectively prevented, and a sufficient amount of dissolved gas can be supplied to the glass to improve the defoaming and clarification properties.

[0133] The method for adding water vapor to the melting atmosphere is not particularly limited, but examples include a method in which a connecting pipe is inserted into the crucible from an opening provided in the melting apparatus, and water vapor is supplied to the space within the crucible through this pipe as necessary.

[0134] The melting step may be accompanied by bubbling in order to stir the molten material. The bubbling during melting may be continued even after the blended materials are melted. By stirring the molten material in the melting step, oxidation of the glass components progresses while oxidation of platinum derived from the platinum crucible is suppressed. This is because the glass components tend to be more easily oxidized than platinum. As a result, the reduction reaction of the glass components is suppressed to reduce the reduction color, and the dissolution of platinum into the molten material is suppressed to reduce coloring derived from platinum.

[0135] The gas used for bubbling is not necessarily limited, and any known gas can be used, including, for example, nitrogen, carbon dioxide, inert gases such as argon and helium, air, and water vapor.

[0136] By using a gas containing water vapor as the bubbling gas, the βOH value of the final optical glass can be increased, the dissolution of platinum into the glass can be effectively prevented, and a sufficient amount of dissolved gas can be supplied to the glass to improve the defoaming properties and clarification.

[0137] The content of water vapor in such a gas containing water vapor is preferably 10% by volume or more, more preferably 20% by volume or more, even more preferably 30% by volume or more, even more preferably 40% by volume or more, even more preferably 50% by volume or more, even more preferably 60% by volume or more, still more preferably 70% by volume or more, particularly preferably 80% by volume or more, and even more particularly preferably 90% by volume or more. The higher the content of water vapor, the more preferable it is, and by keeping it within the above range in particular, the βOH value of the finally obtained optical glass can be increased.

[0138] The molten material obtained by the rough melting is quenched and crushed to produce cullet. The cullet is then placed in a platinum crucible, heated, and remelted to produce molten glass, which is then clarified and homogenized, and then molded and slowly cooled to produce optical glass. Known methods may be used to mold and slowly cool the molten glass.

[0139] As long as a desired glass component can be introduced into the glass in a desired content, the compound used when preparing the batch raw materials is not particularly limited. Examples of such compounds include oxides, carbonates, nitrates, hydroxides, and fluorides.

[0140] (Manufacturing of optical elements, etc.) To manufacture an optical element using the optical glass according to the embodiment of the present invention, a known method may be applied. For example, the above-mentioned molten glass is poured into a mold and molded into a plate to manufacture a glass material made of the optical glass according to the present invention. The obtained glass material is appropriately cut, ground, and polished to manufacture cut pieces of a size and shape suitable for press molding.

[0141] The cut piece is heated and softened, and press molded (reheat pressed) by a known method to produce an optical element blank having a shape similar to that of an optical element. The optical element blank is annealed, The optical element can be manufactured by grinding and polishing using a known method.

[0142] The cut pieces can be roughly polished (barrel polished) to make the weight uniform and to make it easier to apply a release agent to the surface, then reheated and softened glass can be press-molded into a shape that approximates the shape of the desired optical element, and finally ground and polished to produce an optical element.

[0143] Alternatively, a predetermined weight of molten glass may be separated onto a mold and directly press-molded, and finally ground and polished to produce an optical element.

[0144] The optically functional surface of the prepared optical element may be coated with an anti-reflection film, a total reflection film, or the like depending on the intended use. EXAMPLES

[0145] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.

[0146] Glass samples having the glass compositions shown in Table 1 were prepared by the following procedure, and various evaluations were carried out.

[0147] [Optical glass manufacturing] (Example 1-A) First, oxides, hydroxides, carbonates, and nitrates corresponding to the constituent components of the glass were prepared as raw materials, and the raw materials were weighed and mixed so that the glass composition of the resulting optical glass would be each composition shown in Table 1, and the raw materials were thoroughly mixed. The thus obtained mixed raw materials (batch raw materials) were placed in a platinum crucible, heated at 1250°C to 1400°C for 2 hours to melt and form molten glass (melting process), and stirred at 1300°C to 1400°C for 1 to 2 hours to homogenize and clarify (homogenization and clarification process). The molten glass was cast into a mold preheated to an appropriate temperature. The cast glass was heat-treated for 30 minutes at a temperature 100°C lower than the glass transition temperature Tg, and allowed to cool to room temperature in a furnace to obtain a glass sample.

[0148] The following operations were carried out in the melting process, homogenization and clarification process.

[0149] A platinum pipe was inserted from the outside of the melting furnace into the platinum crucible placed inside the furnace, and water vapor was supplied to the space inside the platinum crucible through the platinum pipe. The flow rate of the supplied water vapor was 25 cc / min.

[0150] Nitrogen was supplied to the space in the platinum crucible through the platinum pipe, and water vapor was bubbled into the melt from a tube installed at the bottom of the crucible. The flow rates of the supplied nitrogen and water vapor were 30 L / min for nitrogen and 0.1 cc / min for water vapor.

[0151] Furthermore, glass samples were prepared by changing the presence or absence of additives and the conditions in the melting process and the homogenization and fining process as shown in Tables 2 to 4. Specifically, the conditions are as follows.

[0152] (Example 1-B) A blended raw material corresponding to No. 1 in Table 1 was placed in a platinum crucible together with additives shown in Table 2, and heated and melted under each of the conditions 1-1 to 1-9 in Table 2 to form molten glass (melting process), and the mixture was stirred to homogenize and refined (homogenization and clarification process). Except for this, glass samples were obtained in the same manner as in Example 1-A.

[0153] (Example 1-C) The raw materials corresponding to No. 2 in Table 1 were placed in a platinum crucible together with the additives shown in Table 3, and were heated and melted under each of the conditions 2-1 to 2-4 in Table 3 to form molten glass (melting process), and the glass was stirred to homogenize and refined (homogenization and clarification process) to obtain glass samples in the same manner as in Example 1-A.

[0154] (Example 1-D) A blended raw material corresponding to No. 4 in Table 1 was placed in a platinum crucible together with additives shown in Table 4, and heated and melted under each of conditions 4-1 to 4-5 in Table 4 to form molten glass (melting process), and the mixture was stirred to homogenize and refined (homogenization and clarification process) to obtain a glass sample in the same manner as in Example 1-A.

[0155] [Confirmation of glass composition] The content of each glass component in the obtained glass sample was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), and it was confirmed that each composition was as shown in Table 1.

[0156] [Measurement of Pt content in glass] The platinum (Pt) content in the glass was quantified by inductively coupled plasma mass spectrometry (ICP-MS). The quantitative results are shown in Tables 1 to 4.

[0157] [Confirmation of defoaming and clarification effects] For the obtained glass samples, the number of bubbles observed inside the glass was counted, and the number of bubbles (residual bubbles) contained per unit mass (kg) was calculated. The calculation results are shown in Tables 2 to 4.

[0158] [Optical property measurements] The obtained glass samples were measured for βOH, λ70, T400 and T450. The obtained glass samples were further annealed at 710°C for 72 hours, and then The samples were cooled to room temperature in a furnace at a rate of -30°C / hour to prepare annealed samples, and their refractive indices nd, ng, nF and nC, Abbe numbers νd, λ70 and T400 were measured.

[0159] (i) Refractive index nd, ng, nF, nC and Abbe number νd The refractive indices nd, ng, nF, and nC of the annealed sample were measured by the refractive index measurement method of JIS B 7071-1, and the Abbe number νd was calculated based on the formula (1). The results are shown in Table 1. νd=(nd-1) / (nF-nC) (1)

[0160] (ii) βOH The glass sample was processed into a plate-shaped glass sample having a thickness of 1 mm and parallel optically polished flat surfaces. Light was applied perpendicularly to the polished surface of the plate-shaped glass sample, and the external transmittance A at a wavelength of 2500 nm and the external transmittance B at a wavelength of 2900 nm were measured using a spectrophotometer, and βOH was calculated according to the following formula (2). The results are shown in Tables 1 to 4. βOH = -[ln(B / A)] / t (2)

[0161] In the above formula (2), ln is the natural logarithm, and the thickness t corresponds to the distance between the two planes. The external transmittance includes the reflection loss on the glass sample surface, and is the ratio of the intensity of the transmitted light to the intensity of the incident light entering the glass sample (transmitted light intensity / incident light intensity).

[0162] (iii) λ70 The glass sample obtained in Example 1-A was processed to have a thickness of 10 mm and parallel optically polished flat surfaces, and the spectral transmittance was measured in the wavelength range from 280 nm to 700 nm. The intensity of the light beam perpendicularly incident on one of the optically polished flat surfaces was defined as intensity A, and the intensity of the light beam emerging from the other flat surface was defined as intensity B, and the spectral transmittance B / A was calculated. The wavelength at which the spectral transmittance was 70% was defined as λ70. The spectral transmittance also includes the reflection loss of the light beam on the sample surface. The results are shown in Table 1.

[0163] For the glass samples obtained in Examples 1-B to 1-D, λ70 was measured before annealing (before heat treatment) and after annealing (after heat treatment) in the same manner as described above. Tables 2 to 4 show the λ70 before annealing (before heat treatment) and after annealing (after heat treatment).

[0164] (iv) T400 For the glass sample obtained in Example 1-B, T400 was measured before annealing (before heat treatment) and after annealing (after heat treatment). Specifically, the glass sample or annealed sample was processed to have a thickness of 10 mm and parallel optically polished flat surfaces, and the spectral transmittance at a wavelength of 400 nm was measured. Note that the spectral transmittance also includes the reflection loss of light rays on the sample surface. Table 2 shows the T400 before annealing (before heat treatment) and after annealing (after heat treatment).

[0165] (v) T450 The glass sample obtained in Example 1-A was processed to have a thickness of 10 mm and parallel, optically polished flat surfaces, and the spectral transmittance at a wavelength of 450 nm was measured. The spectral transmittance includes the reflection loss of light on the sample surface. The results are shown in Table 1.

[0166] [Table 1]

[0167] [Table 2]

[0168] [Table 3]

[0169] [Table 4]

[0170] As can be seen from the results in Table 1, by increasing the βOH value by introducing water vapor into the melting atmosphere or by bubbling water vapor into the molten glass, optical glass with little coloring and high transmittance at a wavelength of 450 nm could be obtained.

[0171] The results in Tables 2 to 4 show that by increasing the βOH value of the glass, it is possible to obtain optical glass with little coloration and high transmittance in the visible range without having to perform long-term heat treatment in an oxidizing atmosphere after glass molding.

[0172] Example 2 A glass block of 15 mm x 175 mm x 1500 mm was prepared from glass having the composition No. 1 shown in Table 1 and prepared under condition 1-1 in Table 2, and then cut into 5 equal parts to obtain 5 glass blocks of 15 mm x 175 mm x 300 mm. Five samples 1 to 5 for refractive index measurement were prepared using each of the 5 glass blocks, and the refractive index nd of each sample was measured. The refractive index distributions of samples 2 to 5 were as follows, based on the refractive index nd of sample 1, which was at one of the two ends before cutting.

[0173] The difference in refractive index nd between sample 2, taken from a portion adjacent to sample 1, and sample 1 was +0.00001; the difference in refractive index nd between sample 3, taken from the center, and sample 1 was +0.00002; the difference in refractive index between sample 4, taken from a portion adjacent to sample 3, and sample 1 was 0.00000; and the difference in refractive index between sample 5, taken from the opposite end of sample 1 of the two ends before cutting, and sample 1 was -0.00003. As described above, the refractive index distribution at five locations was 0.00005.

[0174] When the refractive index distribution was measured in the same manner for glass having the composition No. 1 shown in Table 1 and produced under conditions 1-2 to 1-9 in Table 2, the refractive index distribution at five points was within 0.00005.

[0175] Furthermore, when the refractive index distribution was measured in the same manner for glasses having each of the compositions No. 2 to 17 shown in Table 1 and produced under the conditions of Example 1-A, the refractive index distribution at five points was within 0.00005.

[0176] Example 3 Lens blanks were prepared by a known method using each of the optical glasses prepared in Examples 1-A to 1-D, and the lens blanks were processed by a known method such as polishing to prepare various lenses. The optical lenses produced include various lenses such as a biconvex lens, a biconcave lens, a plano-convex lens, a plano-concave lens, a concave meniscus lens, and a convex meniscus lens. By combining each lens with a lens made of a different type of optical glass, secondary chromatic aberration can be effectively corrected.

[0177] In addition, because the glass has a low specific gravity, each lens is lighter than a lens having the same optical properties and size, and is suitable for use in various imaging devices, particularly autofocus imaging devices because of its energy saving potential, etc. In the same manner, prisms were produced using the various optical glasses produced in Examples 1-A to 1-D.

[0178] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.

[0179] For example, by adjusting the composition as described in the specification to the glass compositions exemplified above, an optical glass according to one aspect of the present invention can be produced. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. The Abbe number νd is 32.25 or less, B 2 O 3 3 to 45 mass% of La 2 O 3 Contains 20 to 60 mass% TiO 2 , Nb 2 O 5 , W.O. 3 and Bi 2 O 3 At least one oxide selected from the group consisting of The content of P2O5 is 2 mass% or less, The value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 That is, optical glass. βOH=-[ln(B / A)] / t...(2) (In formula (2), t represents the thickness (mm) of the glass used in measuring the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to the thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to the thickness direction. In addition, ln is the natural logarithm.)

2. SiO 2 The optical glass according to claim 1, comprising 0.1 to 25 mass % of

3. SiO 2 0.5 to 15 mass% of B 2 O 3 3 to 30 mass% of La 2 O 3 The optical glass according to claim 1, comprising 20 to 60 mass % of

4. In mass %, B 2 O 3 The content of SiO 2 The optical glass according to any one of claims 1 to 3, wherein the content of

5. B 2 O 3 and La 2 O 3 TiO relative to the total content 2 The mass ratio of the content [TiO 2 / (B 2 O 3 +La 2 O 3 5. The optical glass according to claim 1, wherein the refractive index is 0.030 or more.

6. The Abbe number νd is 20 to 32.25; 6. The optical glass according to claim 1, having a refractive index nd of 1.75 to 2.

50.

7. Nb 2 O 5 and TiO 2 The optical glass according to any one of claims 1 to 6, wherein the total content of is 13 mass % or more.

8. Nb 2 O 5 and TiO 2 The optical glass according to any one of claims 1 to 7, wherein the total content of is 40 mass % or less.

9. Nb 2 O 5 , TiO 2 , W.O. 3 and Bi 2 O 3 9. The optical glass according to claim 1, wherein the total content of is 40 mass % or less.

10. Nb 2 O 5 , TiO 2 , W.O. 3 and Bi 2 O 3 The optical glass according to any one of claims 1 to 9, wherein the total content of is 1.0 mass % or more.

11. B 2 O 3 , La 2 O 3 , SiO 2 , P 2 O 5 , Al 2 O 3 , ZnO, BaO, MgO, CaO, SrO, Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 , ZrO 2 , TiO 2 , Nb 2 O 5 , W.O. 3 , Bi 2 O 3 , Ta 2 O 5 , Li 2 O, Na 2 O.K. 2 O, Cs 2 O, Sc 2 O 3 , HfO 2 , Lu 2 O 3 and GeO 2 The optical glass according to any one of claims 1 to 10, wherein the total content of is more than 95 mass %.

12. The Abbe number νd is 32.25 or less, B 2 O 3 3 to 45 mass% of La 2 O 3 20 to 60 mass% of TiO 2 and ZnO is more than 0 mass%; Nb 2 O 5 , TiO 2 , W.O. 3 and Bi 2 O 3 TiO relative to the total content 2 The mass ratio of the content [TiO 2 / (Nb 2 O 5 + TiO 2 +W.O. 3 +Bi 2 O 3 ) is 0.4 or more, P 2 O 5 The content is 2% by mass or less, The value of βOH shown in the following formula (2) is 0.1 to 2.0 mm -1 That is, optical glass. βOH=-[ln(B / A)] / t...(2) (In formula (2), t represents the thickness (mm) of the glass used in measuring the external transmittance, A represents the external transmittance (%) at a wavelength of 2500 nm when light is incident on the glass parallel to the thickness direction, and B represents the external transmittance (%) at a wavelength of 2900 nm when light is incident on the glass parallel to the thickness direction. In addition, ln is the natural logarithm.)

13. 13. The optical glass according to claim 1, wherein the platinum (Pt) content is less than 10 ppm by mass.

14. 14. The optical glass according to claim 1, which has a volume of 100 ml or more and a refractive index distribution of 0.00050 or less.

15. An optical element comprising the optical glass according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Optical glass, glass gob for press forming, optical part, and methods for manufacturing glass shaped article and optical part

    JP2006225220A

  • Optical glass, glass gob for press molding, glass molding, optical element and method for producing them

    JP2007112697A

  • Method for producing glass

    JP2009073674A

  • Optical glass, glass gob for press-molding, optical element and method for manufacturing the same, and method for manufacturing optical element blank

    JP2010083705A

  • Optical glass, preform material, and optical element

    JP2011026185A